Development of Visible Light Absorption Measurement for Concentrated Dye Solution based on Attenuated Total Reflection Technique and Improvement on its Analysis Method - Hendro Hendro; Mitra Djamal; Wirawan Wirawan; Rahmat Hidayat (Indonesian Journal of Physics, 2008)
An absorption measurement working in ATR (Attenuated Total Reflection) mode has been design for characterization of concentrate dye solution. The system consists of a visible light system as polychromatic wave source, an ATR plate made up from glass or polymer, a spectrometer with a CCD detector. The system is connected to a computer for measurement and data processing. Some commercial inks measured by this ATR system showed absorption spectra which are in agreement with the color of the inks. The absorption parameter will be determined from the incident and reflection beam intensities measured at incident angle larger than the critical angle. We have also carried out Poynting vector analysis and we will show that the energy flow in the normal direction of the interface is not zero. The energy flow, however, decreases along the normal direction of the interface, indicating energy loss due to light absorption in the sample medium. The amount of energy loss depends on the attenuation index or absorption parameters, which is important for formulating the relation between the measured intensities and absorption parameters.